Integration of Building Information Modelling and Geographic Information System at Data Level Using Semantics and Geometry Conversion Approach Towards Smart Infrastructure Management - Zhu, Junxiang (Curtin University, 2018)
This study integrates Building Information Modelling (BIM)and Geographic Information System (GIS) at data level using an open source approach for geometry transformation and an automatic attribute searching algorithm for semantics transfer for the purpose of facilitating data transformation from BIM to GIS. Based on that, an infrastructure management system has been developed using Web GIS technology in conjunction with the models created by BIM and transformed into GIS using the proposed approach.